CONTACT AND CONTACTLESS INVESTIGATIONS OF MANUFACTURED HIGH-PRECISE SURFACE STRUCTURES - Durakbasa, M. N.; Osanna, P. H.; Yurci, M. E.; Aksoy, P. (IMEKO, 2009)
Surface roughness is the measure of the fine irregularities of a surface. Correct function of the manufactured component is critically dependent on its degree of roughness. There are different techniques applicable for surface metrology analysis. This paper presents the analyses of manufactured high-precise surface structures using the results of contact and contactless measurement techniques. The surface structure is primarily a function of the used production processes. During this experimental work, all measured surface roughness parameters have been analyzed by using SPSS 15 statistically. Linear Regression of Ra parameter estimated the coefficients of the linear equation, involving a few independent variables (feed in mm, periodicity, type of material, contrasting, type of production process etc.), that best predicted the value of the dependent variable and the mathematical model giving the values of roughness parameter has been established in terms of feed in mm, the periodicity, contrasting and type of material as a result of the statistical analyses in this experimental study.
Keywords: surface metrology; surface analysis; contact and contactless measurement; Instruments & Instrumentation